Intercultural communicative competence among Malaysian primary esl learners from teachers’ perspective - Siaw Jun Ning; Megawati Soekarno (Human Resource Management Academic Research Society, 2024)
Intercultural communicative competence (ICC) has emerged as a prominent educational objective globally, emphasising the importance of effective communication in diverse cultural and linguistic contexts. Recognising the influential role educators play in learners’ development and achievements, this study explores ICC from English as a Second Language (ESL) teachers’ perspective in primary education setting and investigate their perceptions and pedagogical practices in cultivating this competence in the classroom. This qualitative research engaged nine primary ESL teachers selected through purposive sampling technique. Data collection involved semi-structured interviews and document analysis, with thematic analysis employed for data interpretation. The findings revealed a positive response from Malaysian primary ESL teachers towards ICC development in the classroom. Results also highlighted diverse materials and pedagogical practices employed by the teachers to foster the competence. Additionally, the teachers affirmed the imperative of enhancing ICC among learners at primary school level. This research contributes valuable insights into the perspectives and practices of primary ESL teachers, shedding light on their pivotal role in fostering learners’ ability to communicate effectively across cultural boundaries.